Effectiveness of Mechanical Waves Teaching Materials Using Direct Teaching to Improve Problem-Solving Skills of Students - Norma Norma; Sarah Miriam; Suyidno Suyidno; Dewi Dewantara (Universitas Lambung Mangkurat, 2024)
One of the skills in physics learning is problem-solving skills. However, this skill is not sufficiently trained at school. Therefore, this study aims to analyze the effectiveness of mechanical wave teaching materials that apply direct teaching models to improve students' problem-solving skills. This is a quantitative descriptive research with one group pre-test post-test design on 28 class XI MIA 2 SMA Negeri 1 Alalak students. According to Heller, data collection was obtained through problem-solving tests using indicators of problem-solving skills: visualizing problems, describing problems, planning solutions, implementing solutions, and evaluating problems. The study results stated that the mechanical wave teaching materials effectively improved students' problem-solving problem-solving by producing a problem-solving test N-gain score of 0.83 with a high category. This also shows an increase in students' problem-solving skills. Thus, teaching materials for mechanical waves using the direct teaching method are effectively used in physics learning to improve students' problem-solving skills at school.